Outsourcing Decisions in the UK Textile Industry: The Four Routes to Success? - Ashby, Alison (2005)
There has been an observed increase in the use of outsourcing within the UK textiles industry and via an industry case study this dissertation will investigate how, what and why UK textile firms decide to outsource. Focusing on manufacturing, recognised as the most commonly outsourced function the study will seek to establish the criteria firms apply when making outsourcing decisions and will investigate the role and relevance of established management theory to this process. Through analysis of theory and real business practice guidelines will be developed to aid managers faced with making similar decisions. The implications of outsourcing for both individual firm and the UK textile industry as a whole will also be discussed.